Analisis Penggunaan Aksara Sasak Dalam Keseharian Masyarakat Lombok Barat Di Era Globalisasi - Ismi, Haerul; Asrin, Asrin; Widodo, Arif (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Sasak script is a cultural heritage of the Sasak tribe that has an identity, is unique and deserves to be preserved. The existence of the Sasak script is currently increasingly eroded along with the development of globalization and modernization in society. In fact, many young people do not know the Sasak script both in the form of writing and pronunciation. This study aims to determine the extent to which this Sasak script still survives in society in the current era of globalization and modernization. This study used descriptive qualitative method. Data collection using surveys and interviews. The respondents of this study were parents and adolescents. The problem being studied is how is the interest of the younger generation in knowing Sasak characters? The results of this study indicate that the younger generation's interest in knowing Sasak characters is very low. Indicators that show the low interest of the younger generation in knowing Sasak characters include: the younger generation perceives ancient and traditional Sasak characters, the occurrence of globalization and modernization, the lack of storytellers from ancient parents. Based on the results of the research that has been done, it takes several efforts to arouse the interest of the younger generation in knowing the Sasak script so that it is not eroded, one of which is the use of information technology such as creating creative content about Sasak script then uploading it on a YouTube or Instagram account to attract youths, making books. specifically about the Sasak script